A new broadband dual‐layer monoplolar circular patch antenna with slot coupling. Issue 1 (January 2017) - Chen, Jie; Liu, Juhua
ABSTRACT: A new center‐fed dual‐layer circular patch antenna is proposed for bandwidth enhancement. The proposed antenna consists of a circular ground plane, a slotted circular patch on the lower layer and a parasitic circular patch on the top layer. The slotted circular patch is fed with a coaxial probe. With the help of the slots introduced to the lower patch, the parasitic patch on the top layer is strongly coupled. With the strong coupling of the two patches, a broadband is obtained. A prototype is fabricated. The measured results show that a wide bandwidth of 25% is obtained. Within the bandwidth, the measured peak gain is in the range of 6.2–8.7 dBi. The antenna produces an omnidirectional pattern in the horizontal plane, similar to that generated by a conventional monopole antenna. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:40–43, 2017